ECO-FRIENDLY ATTITUDE AND RESPONSE BEHAVIOURS OF GREEN HOTEL GUEST IN MALAYSIA - Nor Amira Mohd Razali; Aslinda Mohd Shahril; Marlisa Abdul Rahim; Harnidah Samengon (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study attempts to understand the underlying factor that lead to the green hotel consumption by Malaysian green hotel guests. There were three research objectives in this study: 1To examine the relationship between eco-friendly attitudes with intention to stay at green hotel;2) To examine the relationship between guests eco-friendly attitudes with willingness to pay more for green hotel; and 3) To examine the relationship between eco-friendly attitudes with engagement in positive word-of-mouth towards green hotel. An online surveyed was employed to gather data from 210 guests purposively and subsequently analyzed by using SPSS. This study demonstrates that guest eco-friendly attitude was one of the factors that influence their intention to stay, willingness to pay more and engage in positive word-of-mouth about green hotel. Besides that, age also plays a significant role in visiting green hotel where findings showed that customer aged 40 and above tend to show preferences in visiting and pay more for green hotels compared to the young generation for Malaysian context. This study contributes to the existing theory and practice by providing useful insights about the guest eco-friendly attitude that influence their intention to stay, willingness to pay more and engage in positive word-of-mouth about green hotel.